The Influence of Silt Layer Orientation on Slope Stability in Shale Formations - Alam , A K M Badrul; Fujii , Yoshiaki; Li , Zhixue; Dipu , Nahid Hasan; Islam, Md Tajib Ul; Razo, Shakil Ahmed (MIST International Journal of Science and Technology, 2025)
Shale rock masses often include silt layers, impacting slope stability in construction and mining. Analyzing their interaction is crucial for long-term stability. This study used an elasto-plastic model, incorporating the stress transfer method and Coulomb's criterion. It computed stress distribution, assessed failure potential, and identified vulnerable regions. A shale rock mass ranging from 14.75 to 16.75 meter thick, with silt layers varying from 0.36 to 0.5 meter thick was considered in the model. It examined four silt layer conditions: horizontal (SilHL), vertical (SilVL), in-facing (SilIN), and out-facing slope (SilOUT). Mechanical parameters like Uniaxial Compressive Strength (UCS), Tensile Strength (TS), and Young’s modulus (E) were adjusted for varied scenarios: UCS (0.5 to 5 MPa), and E (6 to 60 MPa), keeping UCS/TS = 5 for all the conditions. In the elasto-plastic analysis, overall reductions of 20%, 40%, 60%, 80%, and 90% in E, UCS and TS were evaluated, taking into consideration the temporal degradation. The findings for SilHL indicate that: (i) when the E, UCS, and TS of the silt layer and shale were equivalent, significant structural failure occurred at 60% reduction, with pronounced collapse at 80% and complete failure at 90%; (ii) a lower E in the silt layer with equivalent strength to shale showed no significant differences; (iii) reductions in both E and UCS for the silt layer also revealed no notable differences. For SilVL, the results were similar, with (i) consistent effects as SilHL; (ii) slippage occurring with a lower E for the silt layer; and (iii) bitension failure and toppling observed when the silt layer's strength was one-tenth that of shale. In SilIN, similar patterns emerged, with slippage and tension failures noted under reduced E and UCS conditions. For SilOUT, results mirrored SilHL, with tension failures and divergence in failure patterns under reduced E and UCS. The results of this study indicate that slope failure scenarios involving shale with a silt layer can be effectively simulated using the elasto-plastic method, particularly by incorporating reductions in strength and Young’s modulus. Furthermore, these findings highlight the critical need for additional research on specific slope configurations to refine design methodologies and enhance stability assessments within the context of the elasto-plastic model. MIJST, Vol. 13, June 2025 : 49-58 DOI: https://doi.org/10.47981/j.mijst.13(01)2025.551(49-58)